P-14 Getting muddy in the greenfield: Optimising the capacity to build a sustainable advance care planning program in a major metropolitan catholic health care service in Melbourne, Australia. (1st September 2015) - Boughey, M; Scott, C
Abstract : Background: Through the need to develop an acceptable organisational and community policy in alignment with the health service's Mission, a strategic decision to imbed advance care planning policies into practice as a whole of health service, unit based clinical program has presented many challenges for a "greenfield" 880 bed Catholic faith based health service. For St Vincent's Hospital Melbourne, this foundational approach, considered different to approaches adopted in many other institutions is likely to be more successful and sustainable within the organisation and in its long term implementation into clinical practice. Aim: To present a narrative of the factors, 2 years into implementation, that have had to be considered and systematically worked through, to optimise and build capacity to embed its best CARE Advance Care Planning (ACP) policy as a programme. Methods: Review of the best CARE ACP project officer's workplan development and the progress of actions detailed within the plan and minutes of the organisational ACP steering group taken from November 1, 2013 to June 31, 2015. Results: The process demonstrates a significant number of governance, model/framework conceptualisation, communication processes, information technology developments and point-of-care documentation processes needed to be completed as key steps in the 18 month timeline to create a workable and viable clinical program fit for purpose and piloting. Discussion/conclusion: It can be possible to develop a whole of health service, foundational ACP system and implementation program. Sharing the learning's and understandings from our processes, should be helpful for others organisations developing similar approaches.